(untitled) (Research, Society and Development, 2025)
Patients with prosthetic heart valves are highly susceptible to infective endocarditis. The pathogenesis of this condition is associated with transient bacteremia, an event frequently triggered by dental procedures. Such interventions can promote the translocation of pathogenic microorganisms from the oral microbiota into the bloodstream, culminating in endocardial infection. Given this context, this study aimed to critically analyze and synthesize the available scientific knowledge on the role of dentists in caring for patients with prosthetic heart valves, aiming to identify essential care and best clinical practices that ensure safe and effective dental treatment, contributing to the prevention of infective endocarditis and the promotion of the comprehensive health of these patients. The methodology adopted consisted of an integrative literature review, guided by the research question: "How effective are the role of dentists in reducing the incidence of infective endocarditis in patients with prosthetic heart valves?" Studies published in the last 10 years in Portuguese, English, and Spanish were selected based on eligibility criteria applied to the title, abstract, and full text. The search yielded 242 articles, of which 24 were considered eligible. It is concluded that the role of dentists is essential in identifying patients at increased risk for infective endocarditis. Constant updating of clinical guidelines—such as those established by the American Heart Association—and careful adoption of antibiotic prophylaxis are essential to ensure safe dental care and effectively contribute to the prevention of this condition.